Interstitial atoms enable joint twinning and transformation induced plasticity in strong and ductile high-entropy alloys - Li, Zhiming (Sci Rep, 2017)
High-entropy alloys (HEAs) consisting of multiple principle elements provide an avenue for realizing exceptional mechanical, physical and chemical properties. We report a novel strategy for designing a new class of HEAs incorporating the additional interstitial element carbon. This results in joint activation of twinning- and transformation-induced plasticity (TWIP and TRIP) by tuning the matrix phase’s instability in a metastable TRIP-assisted dual-phase HEA. Besides TWIP and TRIP, such alloys benefit from massive substitutional and interstitial solid solution strengthening as well as from the composite effect associated with its dual-phase structure. Nanosize particle formation and grain size reduction are also utilized. The new interstitial TWIP-TRIP-HEA thus unifies all metallic strengthening mechanisms in one material, leading to twice the tensile strength compared to a single-phase HEA with similar composition, yet, at identical ductility.